'Green cities' going greener? Local environmental policy-making and place branding in the 'Greenest City in Europe'. Issue 6 (2nd June 2016) - Andersson, Ida
ABSTRACT: A growing number of cities around the world have taken advantage of their green image of the purpose of place branding. In the research literature, it is suggested that these practices are motivated by place-based competition over financial and social capital, combined with more holistic motives of sustainable urban development. However, although an increasing number of green cities are engaged in place branding, few studies have researched the impact of place branding on environmental policy-making in a city, building up to the question: how is local environmental policy-making affected by green place branding? Addressing this issue, this paper critically investigates how the continuity of local environmental policy-making is affected by place-branding practices. To tackle this task, the paper firstly develops an analytical framework aiming to understand how green cities emerge and become famous based on their policy-making. Secondly, using that framework, this paper present an in-depth case study of a city branding itself as the 'Greenest City in Europe'. Drawing on the growing body of work on green cities, this paper investigates the 'understudied' practice of using policy for the purpose of place branding as well as the impact of place branding 'on the environment'.